Closing the Gaps in Social and Physical Infrastructure for Achieving Sustainable Development Goals in Asia and the Pacific. (December 2019) - Kumar, Nagesh
Despite robust economic growth, poverty reduction and other indicators of socio-economic progress achieved over the past decades, Asia and the Pacific countries suffer from a number of gaps in the access to social and physical infrastructure such as access to healthcare and education, drinking water, sanitation and electricity among other deprivations. The 17 sustainable development goals (SDGs) adopted by the leaders of the member states of the United Nations in 2015 could be timely for the Asia and the Pacific region as they provide an opportunity to close these gaps by focusing on ridding the planet of poverty and hunger and providing a life of dignity to all, 'leaving no one behind'. SDGs provide an opportunity to the region to foster a more balanced and equitable pattern of development. Meeting these ambitions will require policies for inclusive development. Drawing upon recent UNESCAP analysis, this article not only offers an overview of the region's impressive socio-economic achievements but also highlights the gaps that remain to be closed; it also advocates a policy agenda that can help fulfil the ambitions of SDGs.